2021
DOI: 10.1111/acps.13278
|View full text |Cite
|
Sign up to set email alerts
|

Elevated lipids are associated with reduced regional brain structure in youth with bipolar disorder

Abstract: Objective Abnormal blood lipid levels are common in bipolar disorder (BD) and correlate with mood symptoms and neurocognition. However, studies have not examined the lipid–brain structure association in BD or youth. Methods This study examined low‐density lipoprotein (LDL‐C), high‐density lipoprotein (HDL‐C), triglycerides, and total cholesterol (TC) levels in relation to brain structure utilizing T1‐weighted images, among participants ages 13–20 with BD (n = 55) and healthy controls (HC; n = 47). General line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…In line with our results, a lower HDL cholesterol level had been reported in SCZ and BD patients in previous studies. Some research studies have found that reduced HDL levels were associated with smaller hippocampal volume and cognitive deficits in BD patients ( 53 ). Lower levels of HDL cholesterol are correlated with an increased vulnerability to oxidative damage to lipids, proteins, and DNA, and increased immune–inflammatory responses ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our results, a lower HDL cholesterol level had been reported in SCZ and BD patients in previous studies. Some research studies have found that reduced HDL levels were associated with smaller hippocampal volume and cognitive deficits in BD patients ( 53 ). Lower levels of HDL cholesterol are correlated with an increased vulnerability to oxidative damage to lipids, proteins, and DNA, and increased immune–inflammatory responses ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some research studies have found that reduced HDL levels were associated with smaller hippocampal volume and cognitive deficits in BD patients ( 53 ). Lower levels of HDL cholesterol are correlated with an increased vulnerability to oxidative damage to lipids, proteins, and DNA, and increased immune–inflammatory responses ( 53 ). Furthermore, our results showed that lipid profiles had correlations with neutrophils, lymphocytes, monocytes, and platelets, suggesting a link between lipid metabolism and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that sphingolipids and glycerolipids were increased, whereas glycerophospholipids were decreased, in serum samples from patients with BD. Moreover, studies also showed that elevated lipid level is associated with smaller brain structures in patients with BD (37). Future research is needed to verify the changes in the HDL levels of BD patients compared with those of healthy individuals and the speci c mechanisms of lipid changes in the pathogenesis of BD.…”
Section: Discussionmentioning
confidence: 99%
“…MetS is currently considered a major risk factor for the development of chronic diseases that involve high morbimortality, such as T2DM and SMI, 53 and therefore, early detection and 56 The recent development of lifestyle psychiatry is gaining momentum. 57 Lifestyle modifications reportedly have a positive impact on symptom severity and neurocognitive function for individuals with SMI, 58,59 which goes beyond their known efficacy to treat metabolic comorbidities. Moreover, the negative impact of several MetS components on cognition might be prevented with nutritional and dietary interventions specifically designed to improve cognition in individuals with SMI and T2DM.…”
Section: Dependentmentioning
confidence: 99%